La comunicación emotiva en YouTube - Pelttari, Sanna (Modern Language Society of Helsinki, 2026)
La autora defendió su tesis doctoral Comunicación emotiva como espejo de las
relaciones interpersonales en YouTube: Análisis cualitativo de la lengua usada
por los usuarios hispanohablantes de la plataforma en la Facultad de Letras de
la Universidad de Turku el 17 de mayo de 2025. La oponente fue la doctora
Barbara de Cock (Université catholique de Louvain) y la presidenta del tribunal
fue la catedrática y doctora Marjut Johansson (Universidad de Turku). La
tesis doctoral está disponible en la siguiente dirección: https://www.utupub.fi/
handle/10024/180856.1
This doctoral dissertation examines the emotional communication of YouTube users in light of several underlying phenomena, such as the attention economy, parasocial relationships, social capital, emotional capital, and attachment bonds. The findings reveal that both YouTubers and commenters employ similar linguistic and discursive strategies aimed at capturing the interlocutor’s attention and fostering mutual involvement. Emotional expressions—often intense and repetitive—were identified in both videos and comments, although the role of commenters as admirers was particularly prominent in these linguistic practices.